UPAYA PENINGKATAN PRODUKTIVITAS PADI MELALUI VARIETAS UNGGUL BARU MENDUKUNG SWASEMBADA BERKELANJUTAN DI PROVINSI JAMBI - Adri Adri; Yardha Yardha (Jurnal Agroekoteknologi, 2014)
Rice productivity in Jambi Province is still low, it is necessary for improving productivity. One of the efforts to increase the rice productivity in the Jambi Province is through the application of Integrated Crop Management approach of rice accompanied by technical personnel of Department of Agriculture, Extension and Researcher. One form of assistance is carry out adaptation testing new rice varieties specific location. Tests carried out at the VUB highland rice irrigation agro-ecosystem, rainfed, and tidal swamp. The results showed the diversity of productivity between varieties and locations is different. Average productivity new varities tested higher than the average productivity of rice in the Jambi Province. Average productivity of the VUB are; Inpari 15 (5.7 t ha-1GKP), Inpari 17 (7.4 t ha-1GKP), Inpari 21 (5.77 t ha-1GKP), Inpari 18 (7.01 t ha-1GKP), Inpara 1 (7.2 t ha-1GKP), and Inpara 3 (6.2 t ha-1GKP).